Maintenance of memory CTL responses by T helper cells and CD40-CD40 ligand: antibodies provide the key. - Bachmann, M; Hunziker, L; Zinkernagel, R; Storni, T; Kopf, M (2004)
Cytotoxic T lymphocytes (CTL) are essential for control of primary infections by many pathogens and in particular by non-cytopathic viruses. It has been proposed that long-term maintenance of CTL memory and control of lymphocytic choriomeningitis virus (LCMV) is dependent upon the presence of T helper cells and interaction of antigen-presenting cells and CTL via CD40 and its ligand CD40L. However, we demonstrate here that CD40-CD40L interaction maintains CTL memory by induction of virus-specific antibodies. In fact, loss of CTL memory responses and spread of virus in mice lacking CD40 or its ligand is prevented by repetitive therapeutic injections of LCMV-specific antibodies. This indicates that antibodies are essential for long-term control of non-cytopathic virus and to maintain protective memory. Transfer of neutralizing antibodies or induction of antibodies by therapeutic vaccination within weeks after infection may therefore prove beneficial for the treatment of chronic virus infections such as HIV, hepatitis B, and hepatitis C. See accompanying article http://dx.doi.org/10.1002/eji.200324844